Added predictive value of high uric acid for cardiovascular events in the Ambulatory Blood Pressure International Study. Issue 7 (6th June 2019) - Reboldi, Gianpaolo; Verdecchia, Paolo; Saladini, Francesca; Pane, Marina; Beilin, Lawrence J.; Eguchi, Kazuo; Imai, Yutaka; Kario, Kazuomi; Ohkubo, Takayoshi; Pierdomenico, Sante D.; Schwartz, Joseph E.; Wing, Lindon; et al.
Abstract: The prognostic value of uric acid (UA) for cardiovascular events (CVE) is still debated. Our purpose was to investigate the association between UA and CVE in 5243 participants of the ABP‐International study with the main aim of identifying optimal sex‐specific cut‐points. In multivariable Cox analyses, the relationship between CVE and UA as a continuous variable was modeled by including both linear and nonlinear terms. Survival models were also estimated with UA as a categorical variable. Optimal UA cut‐points were determined using an outcome‐oriented approach. During a median follow‐up of 5.9 years, there were 423 CVE (93 fatal). In age‐ and sex‐adjusted Cox models, UA as a continuous variable was a significant predictor of CVE in all individuals and in men and women considered separately. The relationship between UA and CVE was linear ( P ‐value for nonlinearity 0.54 and 0.80 for men and women, respectively). For each 1 mg/dL increase in UA, the relative hazard increase was 16% in men and 19% in women. In fully adjusted models, UA remained a significant predictor of CVE in the whole study cohort. The optimal cut‐point best separating patients at low and high risk of CVE was 6.3 mg/dL for men and 4.4 mg/dL for women. Subjects with high UA had a 38% greater risk of CVE. In a sex‐specific analysis, the association remained significant only in men (hazard ratio, 1.47; P < 0.01). In conclusion, high UA is an independent predictor for subsequent CVE and significantly improves risk discrimination and reclassification over the baseline multivariable model.